Improving the hydrodynamic properties of catamaran ship - assi, ruba (Latakia University Journal -Engineering Sciences Series, 2025)
This research was done to increase the width value between the two hulls of the catamaran ship in order to study its effect on the resistance value of the ship. The goal of this research is to study the effect of increasing the width between the two hulls of catamaran on resistance. This study has been done using the CFD (computational fluid dynamics), where the (Reynolds Averaged Navier Stoke) RANS method and the K-WSST turbulence model have been used to solve the Navier Stokes equations. In the first stag, a full-scale of the catamaran ship has been designed in the Rhinoceros program. Then, the design has been modified to achieve the best streamlining; then the numerical results have been compared with experimental results where a good agreement has been obtained. The width value has been increased from B=11.77m to B=13.27m, where the increase value was 0.1m in each design at a speed of 10m/s, and the distance between the two bodies is 5m, 8.44m,10m,15m at a speed of (3,6,10) m/s. The calculation of the resistance affecting the ship has been carried out using the ANSYS.